Efektivitas Sistem Penerimaan Pajak Bumi dan Bangunan dalam Mengoptimalkan Pendapatan Asli Daerah (PAD) di Kabupaten Serdang Bedagai - Simarmata, Dyahot Fridolinta; Subhilhar, Subhilhar; Thamrin, Muhammad (Universitas Medan Area, 2025)
This study aims to evaluate the effectiveness of the Rural and Urban Land and Building Tax (PBB-P2) collection system in optimizing Local Own-Source Revenue (PAD) in Serdang Bedagai Regency. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The findings indicate that although PBB is a significant source of PAD, its collection system still faces various structural and technical challenges. Key issues include inaccurate property tax data, delays in distributing tax notifications (SPPT), limited information technology infrastructure, and low public fiscal literacy. On the other hand, supporting factors include the local government's commitment, digitalization initiatives, and the involvement of village officials in tax socialization. However, obstacles such as digital infrastructure disparities, insufficient human resources, and weak oversight continue to hinder the system's optimization. The study concludes that improving the effectiveness of the PBB collection system requires comprehensive institutional reform, capacity building for tax officials, data updating, and the development of inclusive and participatory fiscal communication strategies. These efforts are expected to strengthen regional fiscal independence sustainably.